Management of Archaeological Heritage in minimisation and protection interventions - Branco, Gertrudes (2016)
In recent decades, the archaeological activity in Portugal has witnessed a significant increase, mainly as a result of economic development and the increase in public and private construction works. The growing number of archaeological excavations, motivated by minimisation and protection interventions, corresponded to a disinvestment in multi-annual archaeological research projects. For safety reasons, it is not uncommon that archaeological excavations do not provide the ideal conditions for being open to the public, who is interested in knowing the work of archaeologists. In the same way, evidence shows that the knowledge acquired in this work remains in the technical and scientific reports and is not suitable for dissemination among the interested public. Another important issue is related to the management of the large volume of assets collected during archaeological interventions, which conflicts with the lack or shortage of museums and sites dedicated to their exhibition. These are kept in the possession of excavation directors or in government deposits, inaccessible to public enjoyment and knowledge.